2023
DOI: 10.1021/acs.inorgchem.3c01145
|View full text |Cite
|
Sign up to set email alerts
|

Tetravalent Uranium and Thorium Complexes: Elucidating Disparate Reactivities of AnIVCl2 (An = U, Th) Supported by a Pyridine-Decorated Dianionic Ligand

Abstract: Although synthesis, reactivity, and bonding of U­(IV) and Th­(IV) complexes have been extensively studied, direct comparison of fully analogous compounds is rare. Herein, we report corresponding complexes 1-U and 1-Th, in which U­(IV) and Th­(IV) are supported by the tetradentate pyridine-decorated dianionic ligand N2NN′ (1,1,1-trimethyl-N-(2-(((pyridin-2-ylmethyl)­(2-((trimethylsilyl)­amino)­benzyl)­amino)­methyl)­phenyl)­silanamine). Although 1-U and 1-Th are structurally very similar, they display disparate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 61 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…Despite structural similarities, these two complexes exhibit notably different reactivities when interacting with tris(trimethylsilyl)silylpotassium (TMS 3 SiK) . In the case of the U-based complex, the reaction with one equivalent of TMS 3 SiK in tetrahydrofuran (THF) leads to the formation of a dimer as shown in Figure . In contrast, the Th-based complex undergoes a salt elimination reaction with one equivalent of (TMS) 3 SiK, resulting in a thorium-containing molecular complex where the pyridyl group is subjected to a 1,4-addition nucleophilic attack (Figure ).…”
Section: Targeted Properties Of Zr- Th- and U-frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite structural similarities, these two complexes exhibit notably different reactivities when interacting with tris(trimethylsilyl)silylpotassium (TMS 3 SiK) . In the case of the U-based complex, the reaction with one equivalent of TMS 3 SiK in tetrahydrofuran (THF) leads to the formation of a dimer as shown in Figure . In contrast, the Th-based complex undergoes a salt elimination reaction with one equivalent of (TMS) 3 SiK, resulting in a thorium-containing molecular complex where the pyridyl group is subjected to a 1,4-addition nucleophilic attack (Figure ).…”
Section: Targeted Properties Of Zr- Th- and U-frameworkmentioning
confidence: 99%
“…At the same time, while zirconium compounds can certainly serve as a useful surrogate for thorium-based ones in many cases, it is also valuable to view many aspects of thorium chemistry in light of other actinides like uranium, especially considering the distinct properties of actinides influenced by the presence of f -electrons. For example, careful analysis of the literature concerning zirconium- and actinide-based structures sheds light on how even subtle differences in the mentioned aspects (i.e., charge density, Lewis acidity, or oxophilicity) can result in drastically different properties for organometallic complexes, POMs, or MOFs. ,,,,,,, For instance, combining either Zr, U, or Th with identical organic ligands often leads to different metal coordination environments, structural topologies, and chemical stability and reactivity. ,,,,,,, Such differences in the structure and reactivity of Th-, U-, and Zr-based compounds often become even more pronounced upon transitioning from discrete molecular systems (i.e., metal–organic complexes and cages) to extended structures, like MOFs. As a result, the choice of MOF metal nodes based on either Zr, U, or Th can be used as a variable to tailor the material performance toward a desired application by altering properties like gas sorption, density of states near the Fermi edge, stability, and reactivity. ,,,,, Therefore, the common assumption that metal oxidation state and Lewis acidity alone are sufficient to select zirconium as a reliable nonradioactive surrogate for Th-based materials development needs to be considered as a first approximation.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…Currently, there are several screening methods for ion-imprinted polymer functional monomers: 29–31 (1) ultraviolet spectroscopy, which is the most commonly used method for screening ion-imprinted functional monomers; (2) ion simulation technology, where computer simulation software is used to simulate the interaction forces between template ions and some functional monomers and to calculate the magnitude of these forces, enabling the best functional monomers to be selected; (3) nuclear magnetic resonance spectroscopy (NMR), which can also be used to screen functional monomers. 32–36 However, these methods have some limitations. For example, ultraviolet spectroscopy is mainly suitable for the screening of functional monomers containing special functional groups; some substances without absorption peaks in the ultraviolet range cannot be screened by this method.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some related studies have shown that tripod ligands have advantages in the construction of fivecoordinate triangular bipyramidal complexes. [27][28][29][30][31][32] Inspired by previous work, we were interested in preparing a new class of five-coordinate triangular bipyramid mononuclear Dy III -based SIMs with local D 3h symmetry. For deeper understanding of magneto-structural correlation and detailed theoretical elucidations of the dynamic magnetic behaviors in five-coordinate Dy III SIMs.…”
Section: Introductionmentioning
confidence: 99%